PENERAPAN REMEDIAL DALAM MENINGKATKAN NILAI BELAJAR SISWA X AK3 SMK MUHAMMADIYAH 2 PEKANBARU - Putri Clawson; Desy Ardyla (P3M STKIP 'Aisyiyah Riau, 2015)
The purpose of this study are: (1) To find out this picture done in class X AK at SMK Muhammadiyah 2 Pekanbaru in the academic year 2015/2016, (2) To find out this picture using the remedial type (3) To find out this picture done on subjects the economy. This type of research is descriptive research that is using methods that describe, report, and analyze the conditions that took place at the time of this study which are related to the implementation of remedial in improving student learning outcomes at SMM Muhammadyah 2 Pekanbaru Academic Year 2015/2016. Data collection techniques are done using interviews, observation, tests, questionnaires, and documents. The data analysis technique was carried out using qualitative techniques, namely giving a description of remedial implementation in terms of completeness of student learning during the economic learning period. Results of Research conducted the application of remedials in improving the learning outcomes of students of class x ak3 in economic subjects At the Muhammadyah 2 Pekanbaru Senior High School in general was classified as good, meaning that the application of remedial in improving student learning outcomes of class x ak3 was quite good.